Consistency in color parameters of a commonly used shade guide - Esam Tashkandi (Saudi Dental Journal)
Objective: The use of shade guides to assess the color of natural teeth subjectively remains one of the most common means for dental shade assessment. Any variation in the color parameters of the different shade guides may lead to significant clinical implications. Particularly, since the communication between the clinic and the dental laboratory is based on using the shade guide designation. The purpose of this study was to investigate the consistency of the L∗a∗b∗ color parameters of a sample of a commonly used shade guide. Materials and methods: The color parameters of a total of 100 VITAPAN Classical Vacuum shade guide (VITA Zahnfabrik, Bad Säckingen, Germany(were measured using a X-Rite ColorEye 7000A Spectrophotometer (Grand Rapids, Michigan, USA). Each shade guide consists of 16 tabs with different designations. Each shade tab was measured five times and the average values were calculated. Results: The ΔE between the average L∗a∗b∗ value for each shade tab and the average of the 100 shade tabs of the same designation was calculated. Using the Student t-test analysis, no significant differences were found among the measured sample. Conclusion: There is a high consistency level in terms of color parameters of the measured VITAPAN Classical Vacuum shade guide sample tested. Keywords: Color parameters, Shade guide